PENERAPAN TEKNIK RUFFLE DAN UPCYCLE FASHION PADA BUSANA COCKTAIL DRESS TERINSPIRASI DARI AMERICAN BALD EAGLE - Dea Fahira; Cucu Ruhidawati (BAJU: Journal of Fashion and Textile Design Unesa, 2025)
This study explores the application of ruffle techniques and upcycle fashion concepts in designing a cocktail dress inspired by the American Bald Eagle, a symbol of strength and freedom. The ruffle technique, which forms wavy and voluminous fabric details, is applied to represent a majestic appearance of eagle wings. Meanwhile, the upcycling concept is implemented on an unused blazer by adding decorative elements that is not only aesthetically valuable but also functionally renewed. Through the Research Project-Based Learning approach, the design process involves the stages of planning, creation, and design evaluation. The theme of the design, Dark Avant-Garde, emphasizes dramatic and romantic nuances through a combination of dark colors, contrasting textures, and asymmetrical silhouettes. The final result is a two-piece cocktail dress with experimental character, suitable not only for semi-formal events but also for fashion editorials and runway show. This research aims to apply ruffle techniques and upcycle fashion inspired by the characteristics of the bald eagle through a combination of textile manipulation techniques and sustainability principles. Therefore, this study seeks to produce a fashion design that is aesthetic, sustainable, and relevant for fashion enthusiasts.